Global Weak Solutions to the Navier-Stokes-Vlasov-Poisson System - Anoshchenko, O.; Khruslov, E.; Stephan, H. (Журнал математической физики, анализа, геометрии, 2010)
We consider the Navier{Stokes{Vlasov{Poisson system describing the °ow of a viscous incompressible °uid containing small solid charged particles. The existence result for weak global solutions of the corresponding boundary value problem is obtained.